A fiscal capacity for the euro area: Lessons from existing fiscal-federal systems - Pablo Burriel; Panagiotis Chronis; Maximilian Freier; Sebastian Hauptmeier; Lukas Reiss; Dan Stegarescu; Stefan van Parys (European Central Bank (ECB), 2020)
After the financial and economic crisis in Europe, a broad consensus has emerged that a stronger fiscal dimension may be needed to complete the architecture of Economic and Monetary Union (EMU). This paper analyses the performance of interregional transfers in existing fiscal-federal systems, notably in Austria, Belgium, Germany, Spain and the United States, and aims to draw lessons for the design of a euro area fiscal instrument. The empirical risk-sharing analysis in this paper suggests that effective cross-regional stabilisation of asymmetric shocks tends to work via direct cash transfers to households, such as unemployment benefits, which are financed out of cyclical central government taxes and social security contributions. This would suggest that a euro area budgetary instrument for stabilisation should be designed as a tool that enhances the automatic stabilisation capacity in the single currency area. At the same time, it seems important that a prospective central stabilisation instrument for the euro area would be integrated in an overall fiscal policy framework that ensures proper incentives for national policymakers.
Keywords: E62; H11; H77; 330; euro area fiscal capacity; fiscal risk-sharing; fiscal federalism